Teaching Piano to Blind Children: An Analysis of Positive Perceptions Based on Perma Framework in Qingdao, China - Xin, Jiang; Poon, Chiew Hwa Chiew; Cooper, Shelly; Wing, Cheong Ku (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2023)
Blind children can benefit from music education as it enhances their musical skills and auditory abilities. However, blind children in China face challenges in pursuing music education due to issues such as social stigma and lack of qualified teachers. Moreover, research in this area is lacking. On the basis of the PERMA (positive emotion, engagement, relationships, meaning, accomplishment) framework, this study attempts to identify the positive psychology of blind children’s piano learning among teachers, blind students, and parents. This study aims to to fill the research gap of piano learning among blind children. Interviews were conducted with piano teachers, blind students, and their parents (N=56) using a qualitative research methodology through PERMA framework. The data identified that piano teachers’ instruction was influenced by their preparation of teaching and personal attitudes. Findings also revealed that the positive emotion, sense of engagement, and positive relationships, impacted the accomplishment and achievement of all participants. This study demonstrates that teachers’ preparation experience and positive attitudes, engagement, and building rapport with blind children and their parents are crucial to promoting their piano learning. This study offers readers the chance to get insight into the field of piano instruction for the blind as well as illumination from thought and empirical support for piano teachers and music educators in inclusive music education in China.